Pengaruh Kualitas Pelayanan Dan Kepercayaan Pelanggan Terhadap Kepuasan Pelangganpada Pt Kai Commuter Di Stasiun Klender - Muslim, Abdul; Nurkhamidah, Nurkhamidah (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study investigates the impact of service quality and customer trust on customer satisfaction at PT KAI Commuter, Klender Station, using a descriptive analysis and quantitative approach. The population includes passengers at the station, with a sample size of 225 respondents determined through probability sampling. Data analysis employs the Sem Pls program, and hypothesis testing reveals significant findings. The t test indicates that service quality has a positive and significant effect on customer satisfaction (7.001 > 1.970, significance 0.000 < 0.05). Similarly, customer trust shows a positive and significant impact on customer satisfaction (5.522 > 1.970, significance 0.000 < 0.05). Recommendations include improving timeliness and customer assistance while maintaining effective indicators